The Future of Positive Psychology and Disability - Wehmeyer, Michael L. (Frontiers in Psychology, 2021)
For much of the history of the application of psychology to disability, the research and clinical focus of the field was deficits-oriented: documenting what people with disability could not do, proposing theories of why they could not do these things, creating measures to assess this incapacity and incompetence, and building interventions and treatments predicated on disease and pathology. It has been only in the last few decades that conceptualizations of disability allowed for consideration of strengths and positive attributes along with the presence of disability and only in the past two decades that a positive psychology of disability has emerged. This article will briefly summarize the factors that led to the emergence of a focus on the positive psychology of disability and a strength-based approach in the field, examine the state of knowledge and practice as it pertains to the positive psychology of disability, and will examine challenges that serve as barriers to progress in this area and opportunities for advancement. Among these is examining how “optimal human functioning” can be understood in ways that includes, and not excludes, people with disability. The importance of shifting the disability research and practice focus to emphasize flourishing, well-being, and self-determination of and for people with disability will be discussed, as well as the necessity for the field of positive psychology to more aggressively reach out to include people with disability among those populations whom the field values and includes.